L' Homosexualité vue par les homosexuels. - Centre de Culture et de Loisirs (CCL) (Bruxelles : Infor-Homosexualité, 1979)
Fonds Suzan Daniel (FSD)
Speciaal nummer van Rond Point 05(1974)
Frans
Monografie